Social Media in Crisis Communication - Burgess, Jean; Bruns, Axel; Crawford, Kate; Finn, Megan; Monroy-Hernandez, Andres; Palen, Leysia (AoIR Selected Papers of Internet Research, 2013)
The use of social media in crisis communication has developed substantially in recent years; social media have been found to play a role in natural disasters and human-made crisis events ranging from the devastating 2010/11 earthquakes in Christchurch, New Zealand, through the 2011 riots in London and the wider UK, to the 2012 hurricane Sandy on the eastern seaboard of the United States. Approaches by emergency response organisations and other stakeholders to the use of social media in crisis communication continue to vary widely, however: while some such organisations are actively exploring a variety of models for incorporating tools such as Facebook and Twitter into their overall emergency media mix, others have been taking a much more cautious approach and continue to see social media as a potential disruption and source of rumours and misinformation. At the same time, the practice of social media analysis as applied to crisis informatics is growing at an extraordinary rate across the humanities and social sciences - as well as computer science and informatics. This panel brings together a number of recognised experts in the study of social media and crisis communication in order to explore the current state of play across a range of disciplines, organisational contexts and international jurisdictions. The adoption of social media by government and other emergency response organisations is always influenced by the specific local contexts of use - including legal frameworks for public communication by emergency services, current social media demographics and rates of take-up, and the potential utility of social media tools in the specific types of emergency which are most likely to occur in the local region. This panel enables a cross-comparison of emergency services’ assessment of and responses to these factors. The pooling and evaluation of such diverse institutional knowledge and experience on an international level is important as it informs the next stage of social media adoption by emergency organisations. The researchers and research centres gathered for this panel each work closely with a variety of such organisations, and are able to influence further social media strategy development. The papers in this panel offer a range of approaches to the study of social media use in crisis communication, building on empirical research to critique current approaches, propose practical guidelines and to set new intellectual agendas in this rapidly growing field of applied internet research.The panel provides an important opportunity for knowledge sharing between these research groups, as well as with the wider AoIR community.